Rhizosphere biology of aquatic microbes in order to access their bioremediation potential along with different aquatic macrophytes - Sharma, Ruchi; Sharma, Kritika; Singh, Neetu; Kumar, Ajay (Recent Research in Science and Technology, 2013)
Background: Contamination of the aquatic environment by toxic metal ions is a serious pollution problem. Aim: This study reviews the role of different Rhizospheric bacteria in bioremediation along with aquatic macrophytes. Methods and Materials: Literature searches were done to identify relevant studies in the concerned area. Results: Natural resources including plants and microorganisms are extensively explored to combat metal ion pollution. Certain compounds produced by bacteria have been shown to promote plant growth. Rhizospheric micro-organisms are well known for their coexistence with plants and for providing nutrition to plants. It was recently reported that these organisms facilitate the uptake of essential elements, such as iron, copper and zinc. Eichhornia crassipes showed increased removal efficiency of heavy metals through the activity of its Rhizospheric bacteria. The highly versatile metabolic capabilities of fungi and bacteria can be applied to reclaim polluted ecosystems and minimize the potential adverse effects of hazardous chemicals released to the environment. However, sufficient consortia of microorganisms, capable of degrading the contaminant(s), must be present, and environmental conditions conducive to degradation must be maintained. Conclusion: Moreover, the information presented, herein illustrates the potential for Rhizosphere microbial communities to remediate systems through biotransformation of hazardous organic compounds in the root zone. Future research in this area should include investigations of the possible role and characterization of the microorganisms associated with different plant species and different histories of toxicant exposure.